Developing A Calibration Moel of Leaf Water Potensial Determination in Tomato Plants Using Nir Spectroscopy with Temperature Compensation - Diding Suhandy; Takahisa Matsuoka (PERTETA, 2008)
In this study a calibration model with temperature compensation for leaf water potential (LWP) determination in tomato plants was successfully developed. A number of 150 tomato plants (Lycopersicon esculentum ev. Momotaro T-93) were used as samples. The plants were cultivated under same EC level (0.8 dSm-1) in Deep Flow Technique (OFT) using Wagner's pot. For each leaf, the uon-plant